PELATIHAN DESAIN SOLIDWORKS 2D & 3D KEPADA SISWA MENENGAH KEJURUAN DI DESA SEGARAN - Mahendri Cakra Yasa; Rido Budiman; Sya’baningrum Prihartini (An-Nizam, 2022)
The world of education is currently facing an industrial revolution, for the younger generation it is necessary to prepare in terms of abilities in the computer field. For vocational students, the ability that must be improved is to be skilled at using computers to design as a development in drawing technique subjects. Based on the school's mission, one of which is to strive for the quality of vocational education services in accordance with the demands of the business community and the industrial world, so training on computer drawing techniques needs to be added specifically. One of the developments required is skillful use of SolidWork software. Students can improve their skills in using the software by participating in training held by Mechanical Engineering students at UNISMA BEKASI. SolidWork's training method uses direct instruction, which includes orientation activities, presentations, structured exercises, guided exercises, and independent exercises.